Iraq and the crimes of aggressive war : the legal cynicism of criminal militarism / John Hagan, Joshua Kaiser, Anna Hanson. - Hagan, John, 1946-; Kaiser, Joshua, 1985-; Hanson, Anna, 1985- (Cambridge studies in law and society., 2015)
From the torture of detainees at Abu Ghraib to unnecessary military attacks on civilians, this book is an account of the violations of international criminal law committed during the United States invasion of Iraq. Taking stock of the entire war, it uniquely documents the overestimation of the successes and underestimation of the failings of the Surge and Awakening policies. The authors show how an initial cynical framing of the American war led to the creation of a new Shia-dominated Iraq state, which in turn provoked powerful feelings of legal cynicism among Iraqis, especially the Sunni. The predictable result was a resilient Sunni insurgency that re-emerged in the violent aftermath of the 2011 withdrawal. Examining more than a decade of evidence, this book makes a powerful case that the American war in Iraq constituted a criminal war of aggression.